Online patients questions regarding reverse total shoulder arthroplasty pertain to timeline of recovery, specific activities, and limitations - Kyle K. Obana, MD; Dane R.G. Lind, BA; Andrew J. Luzzi, MD; Michaela J. O’Connor, MD; Matthew R. LeVasseur, MD; William N. Levine, MD (JSES Reviews, Reports, and Techniques)
Background: Reverse total shoulder arthroplasty (rTSA) demonstrates favorable long-term data and has outpaced anatomic total shoulder arthroplasty and hemiarthroplasty as the most-performed shoulder arthroplasty procedure. As indications and outcomes continue to favor rTSA, patients may turn to the internet as an efficient modality to answer various questions or concerns. This study investigates online patient questions pertaining to rTSA and the quality of the websites providing information. Hypotheses: (1) Questions will pertain to surgical indications, timeline of recovery, and postoperative restrictions; (2) the quality and transparency of online information is largely heterogenous. Methods: Three rTSA searches were entered into the Google Web Search. Questions under the “People also ask” tab were expanded sequentially and 100 consecutive results for each query were included for analysis (300 in total). Questions were categorized based on Rothwell’s Classification and subcategorized by topic. Websites were categorized by source. Website quality was evaluated by the Journal of the American Medical Association (JAMA) Benchmark Criteria. Results: Most questions fell into the Rothwell Fact category (49.7%). The most common question topics were Timeline of Recovery (17.3%), Specific Activities (14.7%), and Restrictions (11.3%). The least common question topics were Anatomy/Function (0.0%), Cost (0.3%), and Diagnoses/Evaluation (0.3%). The most common websites were Medical Practice (45.0%), Academic (22.3%), and Single Surgeon (12.3%). PubMed articles consisted of 41.2% of Government websites. The average JAMA score for all websites was 1.48 ± 1.27. Government websites had the highest JAMA score (3.11 ± 1.01) and constituted 55.9% of all websites with a score of 4/4. Medical Practice websites had the lowest JAMA score (0.99 ± 0.91). Conclusion: Patients are interested in the timeline of recovery, ability to perform specific activities after surgery, and short-term and long-term restrictions following rTSA. Although all patients will benefit from education on ways to perform activities of daily living while abiding by postoperative restrictions, physicians should set preoperative expectations regarding return-to-activity following rTSA in younger, more active patients. Finally, surgeons should provide patients with physical booklets and online information available on their websites to avoid reliance on low-quality online sources.